ChemInform Abstract: A New Solvothermal Synthetic Route Yields the New Thiostannate [La(dien)3]2 [Sn2S6]Cl2. Issue 10 (February 2016) - Pienack, Nicole; Luehmann, Henning; Naether, Christian; Bensch, Wolfgang
Abstract: [La(dien)3 ]2 [Sn2 S6 ]Cl2 (dien: diethylenetriamine) is obtained under solvothermal conditions using cystamine dihydrochloride as the sulfur source together with SnCl2, La(OH)3, and dien (autoclave, 170 °C, 120 h; 50% yield based on La(OH)3 ).